2017
DOI: 10.1007/s40257-017-0258-0
|View full text |Cite|
|
Sign up to set email alerts
|

Calcipotriol Plus Betamethasone Dipropionate Aerosol Foam in Patients with Moderate-to-Severe Psoriasis: Sub-Group Analysis of the PSO-ABLE Study

Abstract: BackgroundFixed-combination calcipotriol 50 μg/g plus betamethasone 0.5 mg/g (Cal/BD) aerosol foam is a new topical treatment for psoriasis. Although moderate-to-severe psoriasis is typically treated with systemic/biologic therapies, a topical treatment that is efficacious in these patients may be a significant cost-saving alternative to systemic therapy.ObjectiveThe objective of this study was to assess the response to Cal/BD foam and gel in patients with moderate-to-severe psoriasis enrolled in the phase III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
4
34
0
1
Order By: Relevance
“…DLQI data to assess the impact of onset of action on HRQoL were from two Phase III trials; therefore, it was a smaller sample size than other data analysed in this study. Nevertheless, together with previously published data, our analysis suggests a potential impact of rapid onset of action on DLQI . In addition, efficacy was not evaluated by study investigators earlier than week 1, so the earliest onset of action in terms of PGA or mPASI is unknown.…”
Section: Discussionmentioning
confidence: 69%
“…DLQI data to assess the impact of onset of action on HRQoL were from two Phase III trials; therefore, it was a smaller sample size than other data analysed in this study. Nevertheless, together with previously published data, our analysis suggests a potential impact of rapid onset of action on DLQI . In addition, efficacy was not evaluated by study investigators earlier than week 1, so the earliest onset of action in terms of PGA or mPASI is unknown.…”
Section: Discussionmentioning
confidence: 69%
“…39 Clinical trials involving Cal/BD aerosol foam have demonstrated that this formulation is safe and well tolerated. Once that the application frequency is reduced by the combination treatment foam, a significant reduction of both active ingredients monotherapies-related adverse events (AEs) is also observed.…”
Section: Safety Datamentioning
confidence: 99%
“…Once that the application frequency is reduced by the combination treatment foam, a significant reduction of both active ingredients monotherapies-related adverse events (AEs) is also observed. 13 AEs were generally of mild or moderate severity, 2,3,25,[37][38][39]43 mostly lesional or perilesional, rarely leading to treatment discontinuation. 3,25,38,39 Skin atrophy, adrenal suppression based on ACTH stimulating test, clinically relevant changes to HPA axis or calcium homeostasis were rarely reported (Table 1).…”
Section: Safety Datamentioning
confidence: 99%
See 2 more Smart Citations